Early Ponseti Technique And Percutaneous Achilles Tenotomy In Neonates With Ctev: A Retrospective Analysis" (Journal of Pharmaceutical Negative Results, 2022)
Background: Among congenital acquired deformities, Congenital Talipes Equinovarus (CTEV) ranks fifth and can be treated both conservatively and surgically. This study emphasizes the conservative management of CTEV using the Ponseti method, commencing treatment during the first week of life, along with percutaneous Achilles tenotomies.Objectives:To assess the results of early application of the Ponseti method and percutaneous Achilles tenotomy, addressing the question of success, recurrence and resistance at the initial stage of CTEV treatment in neonates.Study Design: A retrospective studyPlace and Duration of Study: From 05-January 2021 to 05-July 2021, a retrospective study was conducted on neonates treated for CTEV at Bacha Khan Medical College, Mardan.Methodology: The study included 42 babies (28 boys and 14 girls) over a period of 2 years. Manipulation and weekly casting were performed by well trained orthopedic surgeons. Percutaneous Achilles tenotomy was performed as needed for individual patients. This study examines the outcomes of early commencement of the Ponseti method and percutaneous Achilles tenotomy in treating CTEV.Results: Treating newborns with clubfoot using the Ponseti method, combined with percutaneous tenotomy of the Achilles tendon, resulted in excellent outcomes in 37 cases (88.1%), relapsing in 4 cases (9.5%), and resistance in only 1 case (2.3%). Additionally, the prevalence of bilateral clubfoot was 78.1%, in contrast to 21.9% unilateral clubfoot.Conclusions: The Ponseti method, initiated within the first week of life and supplemented with percutaneous Achilles tenotomy, proved to be a successful approach for treating clubfoot.